Short term fluctuating temperature alleviates Daphnia stoichiometric constraints - Esteban Balseiro (Nature Portfolio, 2021)
Abstract In this study, we analysed how short term temperature fluctuation interacts with nutrient limitation in the vertical migrating Daphnia commutata. We hypothesize that short term (daily) temperature fluctuation will alleviate nutrient limitation. We carried out experiments analysing growth rates, phosphorus and RNA content of D. commutate grown under four different temperature regimes and two P-limited conditions. Our experiments showed that individuals grown under fluctuating temperature grew more than at the mean temperature. We estimated the expected sizes for the 15 °C treatment based on the Q10 and for the fluctuating temperature treatment. These expected sizes for both treatments resulted well below the observed ones. The P and RNA content of individuals grown at 10 °C were significantly higher than those at 20 °C, and when individuals grown at 10 °C were translocated to 20 °C they exerted an increased growth rate. Our results suggest that, under a regime of diel vertical migration, the temperature alternation would allow migrating organisms to alleviate the effect of severe nutrient limitation maintaining population growth. Under a scenario of global warming, where epilimnetic temperatures will increase, lake temperature will interact with nutrient limitation for consumers, but, organisms may be able to face these changes if they can still regularly move from a cold hypolimnion to a warmer epilimnion.